2019
DOI: 10.3389/fmed.2019.00232
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Sarcoidosis: Natural History and Management Implications

Abstract: Introduction: Hepatic granulomas are common in patients with sarcoidosis, but clinically significant liver disease is uncommon and poorly studied. We aimed to characterize the frequency and clinical course of hepatic sarcoidosis in an ethnically diverse population.Methods: This is a retrospective study including all cases of hepatic sarcoidosis in a single center. The median follow-up time was 49 months (4–121). Cases were identified based on ICD-9 and ICD-10 codes for granulomatous hepatitis, sarcoidosis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 22 publications
1
40
0
1
Order By: Relevance
“…PH may complicate hepatic sarcoidosis and may be inaugural in numerous cases. PH affects 10 to 30% of cases of hepatic sarcoidosis in various studies 8,11,13,17,19,20 and may be revealed by esophageal varices with potential gastrointestinal bleeding. Pathogenesis of PH in sarcoidosis is unknown.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 3 more Smart Citations
“…PH may complicate hepatic sarcoidosis and may be inaugural in numerous cases. PH affects 10 to 30% of cases of hepatic sarcoidosis in various studies 8,11,13,17,19,20 and may be revealed by esophageal varices with potential gastrointestinal bleeding. Pathogenesis of PH in sarcoidosis is unknown.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Histological features suggestive of sarcoidosis can be found in most cases. 19,28,30 It can also help to rule out other diagnoses. Prognostic factors of histological data have not been assessed.…”
Section: Histopathological Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…[106][107][108] The most common serum liver function test abnormality with hepatic sarcoidosis is an elevated serum alkaline phosphate in isolation or coupled with a relatively smaller increase in transaminases. 109,110 Occasionally, the serum alkaline phosphatase may reach 5 to 10 times the upper limit of normal with hepatic sarcoidosis, and cholestatic symptoms such as pruritus may develop. 109 Although some have suggested that an elevated serum alkaline phosphatase in a sarcoidosis patient without an alternative etiology confirms liver sarcoidosis, 111 this approach is controversial.…”
Section: Other Organ Screeningmentioning
confidence: 99%